Layer thickness optimization of ceramic composite for body armor by considering volume, weight, and cost - Palaci, Yuksel; Arikan, Mustafa M. (SAGE PUBLICATIONS LTD, 2021)
This study investigates visualization of optimized layer thickness with a ternary diagram by considering Volume, Weight, and Cost priorities to determine the composite structure of alternative ceramics to use in body armor application by using the Digital Logic Method (DLM). Three criterion priorities (volume, weight, cost) have been investigated to help designers decide on optimum ceramic material for their applications. Alumina (Al2O3), silicon carbide (SiC), silicon nitride (Si3N4), and boron carbide (B4C) were analyzed and ranked to decide for material selection based on priorities. The analysis results showed that silicon nitride (Si3N4) had the maximum performance index (PI) point (80.0) based on the volume priority. On the other hand, while boron carbide (B4C) had the maximum PI point (76.4) in terms of the weight priority, alumina (Al2O3) was determined to be the best material according to the cost priority. PI point of alumina (Al2O3) was calculated as 100. A ternary diagram was developed for decision-makers to visualize material selection performances. The optimization of the ceramic composite layer thickness of the alternative ceramic materials is visualized by considering three criteria.
Keywords: Armor; performance; design; composite; material selection; MATERIALS SELECTION; Engineering